Estudo das camadas de lama fluida em portos e canais de navegação - Carneiro, Juliane Castro (2018)
Many ports and navigation channels around the world suffer from silting and the presence of fluid mud layers and this continuous mud deposition can cause reductions in nautical depth. In this context, the existence of fluid mud layers makes the definition of the bottom location ambiguous because the location of interfaces between water, fluid mud and consolidated mud is dynamic and difficult to identify. The present work presents an integrated approach to the study of the fluid mud layers in different port regions and under controlled conditions in a laboratory column. In situ measurements were obtained with acoustic equipment, seismic, density profiles and sampling to characterize the grain size and rheology of the material. The study of the fluid mud is dependent on the rheological characteristics of the sediments, which showed the need to calibrate the methodology individually for each site to be studied. Regarding the detection of mud layers by means of echo-sounder measurements, high frequency return (HF) is associated with the water-mud interface (lutocline), and low frequency return (LF) is a more unstable signal, but correlated with changes in gradients and similar to the values of critical densities identified by the rheological transition measured in the laboratory. Regarding the measurement of the layers, specifically for the Port of Santos, the rheological tests revealed an increase in the yield stress of the samples in the internal region of the estuary. The combination of density profiles and rheological data allowed estimating a potential draft increase of 1.5 m, depending on the location, nautical depth criterion and tide condition. It is expected that the combination of detection and measurement techniques will allow the development of tools for navigation in fluid mud, with potential increase in draft for port areas for safe navigation.